Nasoseptal Flap Reuse for Reconstruction in Revision Endoscopic Skull Base Surgery - Grafmiller, Kevin T.; Kosaraju, Nikitha; Miller, Jessa E.; Suh, Jeffrey D.; Lee, Jivianne K.; Bergsneider, Marvin; Wang, Marilene B. (Journal of Neurological Surgery Part B: Skull Base, 2024)
The nasoseptal flap (NSF) is the “workhorse” for reconstruction in endoscopic skull base surgery. It creates a reliable, watertight closure to prevent cerebrospinal fluid (CSF) leaks. The flap's robust vascular pedicle allows for it to be taken down and reused in subsequent reconstructive surgeries if needed. Previous literature has demonstrated successful reuse of the flap up to 24 months after initial surgery. The present study analyzes a cohort of patients with NSFs that were reused up to 12 years following the initial surgery.A retrospective analysis was performed on patients who underwent revision endoscopic skull base surgery for recurrent tumor at a tertiary academic skull base center. Patient demographics, tumor type, length of time between first and second surgery, and outcomes were evaluated.A total of 15 patients were identified between 2012 and 2022 who underwent revision endoscopic skull base surgery with previous NSFs that were reused for reconstruction. The time interval between surgeries ranged from 9 months to 12 years. There were 12 pituitary adenomas, 2 Rathke's cleft cysts, and 1 craniopharyngioma. One patient developed a CSF leak 5 days postoperatively, which was repaired with an abdominal fat graft, synthetic dural substitute, and a middle turbinate flap. The operative technique for the take-down and reuse of the NSF will be demonstrated.The NSF can be taken down and reused in revision endoscopic skull base cases, even several years after the initial surgery, with excellent coverage of the defect and low incidence of postoperative CSF leak.
Keywords: nasoseptal flap; reuse; pituitary; revision; skull base